Antiviral mechanisms targeting regulatory genes Tat and Rev to defeat latent HIV-1 infected T cells: a literature review - Erly Sintya; Ni Luh Putu Harta Wedari; I Wayan Adi Pranata; Ni Nyoman Sri Budayanti (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2021)
Antiviral drug therapies have been utilized to prevent disease progression in patients positive HIV-1. Various research has been conducted to investigate and develop a potential functional therapy to suppress HIV-1 replication and cure latent HIV-1 in the absence of drugs. Approaches that have been well studied are the anti-HIV-1 which targets RNAs, proteins, or peptides expressed by HIV-1 resistant cells, which can be transplanted to the patients. RNA interference in the form of small RNA has been proven as a promising therapy to prevent HIV-1 replication. It is utilized for therapy using cell transplantation and various gene combinations in clinical trials. However, many studies have been failed to show a successful eradication of latently HIV-1 infected T cells. It is happened due to the virus's ability to escape from antiviral therapies. However, this can be overcome by using a combination of ARTs. On the other hand, genetic editing has been intensively studied since it can cure various diseases caused by genetic or pathogen infections, including HIV type 1. The previous studies have designed gRNA bind to protein Cas type 9 targeting HIV functional genes, Tat and Rev sequences. Various recombination has been introduced to CRISPR-based gene editing to increase the binding affinity and efficiency of Cas9 to target Tat and Rev proteins of their exons. The best approach for the Cas9 targeted Tat and Rev is by utilizing more than one guide RNA. However, Subsequent studies are needed to confirm the ability of Cas9 with various guide RNAs to inhibit virus activation and replication in latent HIV-1. This review aims to describe the mechanisms, advantages, and disadvantages of antiviral therapies that target Tat and Rev as regulatory genes to eradicate latent HIV-1 infected T cells.